Estudo da cristalização da sacarose com adição de antissolvente - Mantilla, Hernán Dario Rojas (Universidade Federal de São Carlos, 2013)
In the study of the sucrose crystallization process, the nucleation phenomena and crystalline growth have been evaluated, when the systems were submitted to different solvent and operational conditions. The main objective of the present work was to study the sucrose crystallization process in solution through the partial change of the solvent. This change occurs through studied with the ethanol addition of a second solvent, a compound that reduces the solute solubility, but that is miscible in the first one. The addition of a second solvent generates a high degree of supersaturation, and promotes the formation of crystalline nuclei of smaller size to be used as seeds in industrial processes. Another objective was to study the flowability properties of particle size by determining the Hausner ratio and repose angle that allows relate some variable results obtained by the crystallization of sucrose. With the obtained results, it would be possible to improve the control of the finally properties of the crystalline product, such as crystal size distribution (CSD), crystalline habit, crystalline fluid inclusions and the formation of crystalline polymorphs.
Keywords: Cristalização; Sacarose; Modelagem Nývlt; Método dos momentos; Crystallization; Sucrose; Antisolvent; Method nývlt; Method of moments; ENGENHARIAS::ENGENHARIA QUIMICA